200 Years of American Financial Panics Crashes, Recessions, Depressions, and the Technology that Will Change it All. - Vartanian, Thomas P. (Prometheus, 2021)
This comprehensive historical account tells the story of 200 years of financial panics in America, from 1819 to COVID-19, showing how and why so many financial crises have occurred in the United States and offering solutions to avoiding these sorts of crises moving forward.